Inhibition of bladder cancer cell proliferation by allyl isothiocyanate (mustard essential oil) - Ventura Savio, Andre Luiz [UNESP]; Silva, Glenda Nicioli da; Favero Salvadori, Daisy Maria [UNESP] (Elsevier B.V., 2015)
Natural compounds hold great promise for combating antibiotic resistance, the failure to control some diseases, the emergence of new diseases and the toxicity of some contemporary medical products. Allyl isothiocyanate (AITC), which is abundant in cruciferous vegetables and mustard seeds and is commonly referred to as mustard essential oil, exhibits promising antineoplastic activity against bladder cancer, although its mechanism of action is not fully understood. Therefore, the aim of this study was to investigate the effects of AITC activity on bladder cancer cell lines carrying a wild type (wt; RT4) or mutated (T24) TP53 gene. Morphological changes, cell cycle kinetics and CDK1, SMAD4, BAX, BCL2, ANLN and S100P gene expression were evaluated. In both cell lines, treatment with AITC inhibited cell proliferation (at 62.5, 72.5, 82.5 and 92.5 mu M AITC) and induced morphological changes, including scattered and elongated cells and cellular debris. Gene expression profiles revealed increased S100P and BAX and decreased BCL2 expression in RT4 cells following AITC treatment. T24 cells displayed increased BCL2, BAX and ANLN and decreased S100P expression. No changes in SMAD4 and CDK1 expression were observed in either cell line. In conclusion, AITC inhibits cell proliferation independent of TP53 status. However, the mechanism of action of AITC differed in the two cell lines; in RT4 cells, it mainly acted via the classical BAX/BCL2 pathway, while in 124 cells, AITC modulated the activities of ANLN (related to cytokinesis) and S100P. These data confirm the role of AITC as a potential antiproliferative compound that modulates gene expression according to the tumor cell TP53 genotype. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Allyl isothiocyanate; Bladder cancer; Cell proliferation; Gene expression; TP53 gene